Kepemimpinan Transformasional sebagai Stimuli Penting Kinerja Karyawan pada Pegawai Sekretaris Jenderal MPR Republik Indonesia - Mochamad Soelton; Eko Tama Putra Saratian; Harefan Arief; Tantri Yanuar Rahmat Syah; Rizka Yunita (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2019)
The purpose of this research is to determine whether Transformational Leadership, Internal Communication, and Work Discipline have any influence on Employee Performance at SETJEN MPR RI employees. The object of this research is the civil servants of MPR RI. This research was conducted on 100 civil servants of MPR RI, data were collected using a questionnaire by using quantitative descriptive approach. Therefore, the data analysis used in this research is statistical analysis in the form of multiple linear regression tests. The results of this research indicate that all three independent variables (Transformational Leadership, Internal Communication, and Work Discipline) positively and significantly affect the dependent variable (Employee Performance) at SETJEN MPR RI employees. Where Work Discipline variable has the greatest influence on Employee Performance at SETJEN MPR RI employees.